Pengaruh Akuntabilitas dan Sistem Pengendalian Internal Terhadap Kinerja Keuangan Pemerintah Daerah (Studi Kasus di Badan Pengelola Keuangan dan Asset Daerah Kota Tidore Kepulauan) - Mattoasi, Mattoasi; Jainuddin, Sitna (Universitas Medan Area, 2024)
The aim of this research is to determine the effect of accountability and internal control systems on local government financial performance. This research uses quantitative research methods. The data source used in this research is saturated sampling. The data analysis technique in this research is descriptive quantitative analysis using uti t statistics, statistical f test, and coefficient of determination test (adjusted R Square) using IBM SPSS 20 for windows. The results of this research show that accountability has a positive and significant effect on local government financial performance, and the control system has a positive and significant effect on local government financial performance and simultaneously accountability and the internal control system have a positive and significant effect on local government financial performance with a value of The determinant is 40.3% while the remaining 60.3% is caused by other factors that are in the theoretical structure but were not tested in this research.